The Periodogram of American Business Activity - Wilson, Edwin B. (Quarterly Journal of Economics, 1934)
I. Various meanings of "period, " 376. — II. Indices referred to "normal" are oscillatory, 378. — III. Statistical findings of cycle analysis, 380. — IV. Hidden periods indeterminable by cycle analysis, 384. — V. The periodogram; general theory, 387. — VI. Periodograms of special types of oscillation, 390. — VII. Illustration of effects of complex interference, 394. — VIII. Two rules and their limitations, 397. — IX. The periodograms for business activity, 400. — X. Details of the periodogram for 1790–1859, 400. — XI. Brief notes on the other periodograms, 405. — XII. Forecasting from the sinusoidal expressions, 407. — XIII. Schuster's statistical test for significance of periods, 409. — XIV. The number of "independent elements" in the series, 411. — XV. A crucial experiment, 413.